轴系摩擦力矩测试台的研制及其实验 - 李荣; 陈文敏; 史士财 (Jixie chuandong)
Using precision force torque sensor and step motor,a friction torque test table for axis system is developed.Measurement range can be adjusted for different axis system through changing mounted position of the force sensor.The test table is used to test the frict ion characteristic of some axis system,and a necessary design basis for control system design is provided.